TG13 indications and techniques for biliary drainage in acute cholangitis (with videos). Issue 1 (January 2013) - Itoi, Takao; Tsuyuguchi, Toshio; Takada, Tadahiro; Strasberg, Steven M.; Pitt, Henry A.; Kim, Myung‐Hwan; Belli, Giulio; Mayumi, Toshihiko; Yoshida, Masahiro; Miura, Fumihiko; Büchler, Markus W.; Gouma, Dirk J.; et al.
Abstract The Tokyo Guidelines of 2007 (TG07) described the techniques and recommendations of biliary decompression in patients with acute cholangitis. TG07 recommended that endoscopic transpapillary biliary drainage should be selected as a first‐choice therapy for acute cholangitis because it is associated with a low mortality rate and shorter duration of hospitalization. However, TG07 did not include the whole technique of standard endoscopic transpapillary biliary drainage, for example, biliary cannulation techniques including contrast medium‐assisted cannulation, wire‐guided cannulation, and treatment of duodenal major papilla using endoscopic papillary balloon dilation (EPBD). Furthermore, recently single‐ or double‐balloon enteroscopy‐assisted biliary drainage (BE‐BD) and endoscopic ultrasonography‐guided biliary drainage (EUS‐BD) have been reported as special techniques for biliary drainage. Nevertheless, the updated Tokyo Guidelines (TG13) recommends that endoscopic drainage should be first‐choice treatment for biliary decompression in patients with non‐surgically altered anatomy and suggests that the choice of cannulation technique or drainage method (endoscopic naso‐biliary drainage and stenting) depends on the endoscopist's preference but EST should be selected rather than EPBD from the aspect of procedure‐related complications. In terms of BE‐BD and EUS‐BD, although there are many reports on the their usefulness, they should be performed by skilled endoscopists in high‐volume institutes, who are good at enteroscopy or echoendosonography, respectively, because procedures and devices are not yet established.